Phenylpyrrole-based HDAC inhibitors: synthesis, molecular modeling and biological studies. (September 2016) - Brindisi, Margherita; Cavella, Caterina; Brogi, Simone; Nebbioso, Angela; Senger, Johanna; Maramai, Samuele; Ciotta, Alfonso; Iside, Concetta; Butini, Stefania; Lamponi, Stefania; Novellino, Ettore; Altucci, Lucia; et al.
Aim: Histone deacetylases (HDACs) regulate the expression and activity of numerous proteins involved in the initiation and progression of cancer. Currently, three hydroxamate-containing HDAC pan-inhibitors have been approved as antitumor agents.Results: We herein present the development of a series of novel phenylpyrrole-based derivatives stemmed from combined computational and medicinal chemistry efforts to rationally modulate HDAC1/6 isoform selectivity. In vitro activity on HDAC1 and HDAC6 isoforms and the effects of selected analogs on histone H3 and α-tubulin acetylation levels were determined. Cell-based data evidenced, for selected compounds, a promising antitumor potential and low toxicity on normal cells.Conclusion: The newly developed compounds represent a valuable starting point for the development of novel anticancer agents.